INSTITUTIONAL ASPECTS OF PUBLIC POLICY MAKING IN ETHNO-NATIONAL SPHERE IN UKRAINE - Meliakov , A. (Pressing Problems of Public Administration, 2020)
The article explores the main stages of the implementation of state policy in ethno-national politics. Particular attention is paid to the period of 2010-2020. It is shown that the status of the central executive body implementing state policy in the field of denominational and inter-ethnic relations has been declining for the most part, i.e. if in 1993 it was a separate ministry, in 2011 it became only a department within the Ministry of Culture.The article proves that the liquidation of the State Committee of Ukraine on Nationalities and Religions in 2010 was a wrong step. The Ministry of Culture, which was responsible for this part of the state’s humanitarian policy in 2010-2020, lacked adequate resources to respond to the complex challenges of inter-ethnic and state-confessional relations.Experts, representatives of the political elite and leaders of national societies and religious associations have consistently stressed the need to restore a separate central body of executive power on ethnopolitics and religions. Their views have been expressed not only in numerous press appearances and in scientific publications, but also in the materials of three parliamentary hearings in 2012, 2013 and 2015.It is proved that the introduction of the position of the Government Ombudsman for Ethnic Policy in 2014 was a kind of compromise between the Government and leaders of NGOs of national minorities. The activities of the Commissioner were not effective due to the following factors: duplication of powers; extremely poor resources; misunderstanding by the government of the place of this institution in the system of bodies implementing state humanitarian policy; brief existence of this position (only less than 10 months). At the same time, the efforts of the Government Ombudsman himself, Gennady Druzenko, were commendable.A new stage in the history of reforming state regulation in the ethno-political sphere began in June 2019, when the establishment of the State Service for Ethno-Politics and Freedom of Conscience began. Interesting components of this stage were holding a second competition for the post of the Chairman; the fact that the competition was won not by a practicing manager but by a scientist; lobbying of one of the candidates for the position by leading representatives of the expert society; the use of lawsuits as a tool to fight for the position of the Chairman of the Office.